Sports Talent Potential in Junior High School Students in Sapuran District, Wonosobo Regency - Septa Katmawanti (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the study: This study aimed to describe the sports talent profiles of seventh-grade male junior high school students in Sapuran District, Wonosobo Regency, and to identify sports disciplines that best match their physical and physiological characteristics using the Sport Search talent identification model. Methodology: A quantitative descriptive design was employed using the Sport Search talent identification model. Data were collected from 300 seventh-grade male students selected through total sampling from four junior high schools in Sapuran District. Ten standardized physical and physiological tests were administered, and data were analyzed using Sport Search normative scoring and talent classification categories. Main Findings: The results revealed that 7 students (2.3%) were categorized as Potential, 53 students (17.7%) as Sufficient Potential, 176 students (58.7%) as Less Potential, and 64 students (21.3%) as No Potential. The most suitable sports identified were sprinting, long jump, high jump, diving, and gymnastics. Overall, the findings indicate a relatively low level of detected sports talent among participants. Novelty/Originality of this study: The novelty of this study lies in the application of the Sport Search talent identification model to a large sample of junior high school students in a rural Indonesian district. The study provides empirical evidence regarding regional sports talent distribution and highlights the importance of structured talent development programs to optimize students’ athletic potential and support long-term sports achievement pathways